2002
DOI: 10.4049/jimmunol.169.6.2892
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant Protein D Reduces Alveolar Macrophage Apoptosis In Vivo

Abstract: Surfactant protein D (SP-D) is a molecule of the innate immune system that recognizes the patterns of surface carbohydrate on pathogens and targets them for phagocytosis and killing. SP-D-deficient mice show an increased number of macrophages in the alveolar space, excess surfactant phospholipid, overproduction of reactive oxygen species, and the development of emphysema. We report here that SP-D-deficient mice have a 5- to 10-fold increase in the number of apoptotic and necrotic alveolar macrophages, as defin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
127
1
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 144 publications
(142 citation statements)
references
References 34 publications
12
127
1
2
Order By: Relevance
“…As has been shown for C1q and SP-D [3,14], we were able to demonstrate that MBL binds to late apoptotic and necrotic cells. MBL binds only to cells positive both for annexin V and nuclear dyes when induced to apoptosis, as well to cells becoming directly necrotic after heat shock.…”
Section: Discussionsupporting
confidence: 83%
“…As has been shown for C1q and SP-D [3,14], we were able to demonstrate that MBL binds to late apoptotic and necrotic cells. MBL binds only to cells positive both for annexin V and nuclear dyes when induced to apoptosis, as well to cells becoming directly necrotic after heat shock.…”
Section: Discussionsupporting
confidence: 83%
“…8 In both in vitro and in vivo studies, SP-D has been reported to bind to, and mediate the clearance of, apoptotic inflammatory cells by alveolar macrophages. [9][10][11] Studies with SP-D knockout mice have also indicated a role of SP-D in the regulation of surfactant lipid homeostasis. 12 Furthermore, Brinker and colleagues 13 found that human SP-D binds to immature bone marrow-derived dendritic cells (DC) in vitro in a dose-, carbohydrate-and calcium-dependent manner, enhancing the phagocytic uptake of Escherichia coli and the antigen presentation to T cells.…”
Section: Introductionmentioning
confidence: 99%
“…The observation that Survanta increased lung cell apoptosis is intriguing because lung surfactant has been reported to promote phagocytic clearance of pathogens, unwanted cells and particles. [21][22][23]35 One possible explanation for this discrepancy is that the amount of Survanta used in the present study may exceed the capacity limit of phagocytic cell clearance. Thus, only a high-dose of Survanta was able to produce apoptosis in vivo.…”
Section: Discussionmentioning
confidence: 71%
“…[21][22][23] To test whether pulmonary surfactant can promote the clearance of apoptotic cells in vivo, we treated rats intratracheally with apoptotic macrophages in the absence or presence of various doses of Survanta. The effect of Survanta administration on lung cell apoptosis was determined by TUNEL.…”
Section: Effect Of Exogenous Surfactant On Lung Cell Apoptosis In Vivomentioning
confidence: 99%
See 1 more Smart Citation